APOBEC3-mediated editing in HIV type 1 from pediatric patients and its association with APOBEC3G/CUL5 polymorphisms and Vif variability - de Maio, Federico Andres (2012)
The APOBEC3 proteins are cytidine deaminases that can introduce G→A mutations in the HIV-1 plus DNA strand. This editing process may inhibit virus replication through lethal mutagenesis (hypermutation), but could also contribute to viral diversification leading to the emergence of escape forms. The HIV-1 Vif protein has the capacity to counteract APOBEC3 factors by recruiting a CUL5-based ubiquitin ligase complex that determines their proteasomal degradation. In this work, we analyzed the APOBEC3-mediated editing in proviral HIV-1 from perinatally infected children (n=93) in order to explore its association with polymorphisms of APOBEC3G and CUL5 genes (APOBEC3G H186R, APOBEC3G C40693T, and CUL5 SNP6), the Vif protein variability, and also the time to AIDS development. To calculate the level of editing, we have developed an index exploiting the properties of a region within the HIV-1 pol gene that includes the central polypurine tract (cPPT). We detected a reduced editing associated with the CUL5 SNP6 minor allele and also with certain Vif variants (mutations at sites 46, 122, and 160), although we found no evidence supporting an impact of APOBEC3 activity on disease progression. Thus, our findings suggest that APOBEC3-mediated editing of HIV-1 could be modulated by host and virus genetic characteristics in the context of pediatric infection.